Intermediate-sulfidation epithermal base and precious metal mineralization in the Qebchaq deposit (NW Qarachaman, East Azerbaijan): Geology, mineralization, and geochemical evidence - Mohammad Sohbatloo; Hossein Kouhestani; Mir Ali Asghar Mokhtari (Journal of Economic Geology, 2023)
Precious and base metal mineralization in the Qebchaq deposit occurred as brecciated quartz-sulfide veins within the Eocene tuff and lava strata, and the Oligocene quartz diorite-gabbro intrusion. Pyrite, chalcopyrite, galena, sphalerite, and gold along with minor realgar, psilomelane, and pyrolusite, are ore minerals; quartz, sericite, chlorite and calcite are gangue minerals. The ore minerals show disseminated, vein-veinlet, brecciated, comb, cockade, colloform, crustiform, plumose, and vug infill textures. Five stages of mineralization can be distinguished at Qebchaq. Stage 1 is represented by silicification of host rocks along with minor disseminated pyrite. Stage 2 is characterized by quartz veins and breccias that contain variable amounts of disseminated pyrite, chalcopyrite, galena, sphalerite ± native gold ± realgar. Stage 3 is marked by quartz-manganese oxides-hydroxides (psilomelane, pyrolusite, braunite) veins and hydrothermal breccia cements. Stage 4 is represented by quartz (calcite-chlorite) vein-veinlets, and stage 5 is characterized by calcite as veinlets and vug infill texture. Wall-rock alterations include silicification, intermediate argillic, carbonate, chlorite and propylitic alteration. Chondrite–normalized trace elements and REE patterns of the mineralized samples and the host rocks are similar and indicate that host rocks are probably involved in mineralization. Characteristics of Qebchaq deposit are comparable with intermediate-sulfidation type of epithermal deposits.